Product Market Power and Tax Avoidance: Market Leaders, Mimicking Strategies, and Stock Returns - Kubick, Thomas R.; Lynch, Daniel P.; Mayberry, Michael A.; Omer, Thomas C. (The Accounting Review, 2015)
ABSTRACT Product market power provides firms with comparative advantages through more persistent profitability and insulation from competitive threats. These advantages likely provide firms with the ability to engage in greater tax avoidance. We present evidence consistent with this hypothesis. We also show that firms mimic the tax outcomes of their product market leaders. Among firms with greater product market power and comparatively high cash tax avoidance, we find stock prices to be less informative and that investors require additional compensation for the risks associated with comparatively high cash tax avoidance. Our results survive numerous robustness tests. Overall, our results suggest that industry dynamics, particularly related to a firm's competitive position, play a meaningful role in corporate tax policy.